Study of user effects on two-port MIMO antennas at 2.4 GHz and 5.8 GHz for Wi-Fi and WLAN applications - Nur Basyirah A. Rahman; Azremi Abdullah Al-Hadi; Rizwan Khan (Institute of Advanced Engineering and Science, 2019)
In this paper, two multiple input multiple output (MIMO) antennas for Wi-Fi/WLAN mobile applications are proposed. The designed two-port MIMO antennas are made up of planar inverted-F antennas (PIFAs). The antenna elements for both designs are symmetrical and placed on the short-edged corners of the substrate used, FR4. The performance of both antennas in the presence of user’s hand is compared in terms of impedance bandwidth and efficiency. An upward shift of up to 0.17 GHz in impedance bandwidth was found for 2.4 GHz and 5.8 GHz antenna. Due to the smaller size of antennas at 5.8 GHz compared to antennas at 2.4 GHz, the antennas are less obstructed by hands and thus the exhibited total efficiency of up to 45.58 % in the presence of human hand. The designed antennas have been fabricated for validation purpose. It is shown that there is a good agreement between simulated and measured results.